The conversion of naphthalene on SOFC anodes and its impact on the cell performance - Li, Yixing; Grimm, Fabian; Karl, Jürgen (Fuel, 2023)
The operation of a SOFC with biomass-derived syngas would provide convincing solutions for combined heat and power production from renewable sources. In principle, the tar components in the wood gas can be reformed on Ni-based SOFC anodes, hence, giving access to additional hydrogen as fuel. The investigation of the kinetic-limited conversion process on anodes and its effect on the electrochemical processes of the SOFC is yet still insufficient. This paper presents the experimental study of the conversion of naphthalene on a single planar electrolyte-supported cell with varying temperature and naphthalene concentration. Thereby the impact of the incomplete conversion of naphthalene on open circuit voltage, methane conversion and cell performance is investigated. A 1-D kinetic model reveals the correlation between the slow naphthalene reforming and the open circuit voltage. The adsorption of naphthalene on the Ni catalyst not only impedes the reforming of methane, but also slows down the kinetics of electrochemical reaction. However, the produced hydrogen from steam reforming reaction is still beneficial in terms of preventing Ni re-oxidation under higher fuel utilization in H2 gas mixture.
CRIS-Team Scopus Importer:2023-03-17
Keywords: Degradation; Fuel utilization; Naphthalene; Solid oxide fuel cell (SOFC); Tar